A gut feeling about insular seizures. (17th June 2011) - Dionisio, S; Koenig, A; Murray, J; Somerville, E
Abstract : A 43-year-old man presented to the Prince of Wales Hospital, Sydney, New South Wales, Australia, after experiencing his first tonic-clonic seizure. For the previous 2 years he had undergone gastroenterological investigation of episodes of gagging associated with hypersalivation and lachrymation, occurring three or four times per week. EEG showed epileptiform discharges in the right anterior temporal region; brain MRI revealed a lesion in the right insular cortex. Video-EEG telemetry demonstrated that the episodes of gagging were focal seizures. Antiepileptic drug therapy resulted in no further episodes occurring over the next 10 months.